The Combined Effect of Cancer and Cardiometabolic Conditions on the Mortality Burden in Older Adults. (19th March 2018) - Raina, Parminder; Gilsing, Anne; Freisling, Heinz; van den Heuvel, Edwin; Sohel, Nazmul; Jenab, Mazda; Ferrari, Pietro; Tjønneland, Anne; Benetou, Vassiliki; Picavet, Susan; Eriksson, Sture; Schöttker, Ben; et al.
Abstract: Background: The number of older people living with cancer and cardiometabolic conditions is increasing, but little is known about how specific combinations of these conditions impact mortality. Methods: A total of 22, 692 participants aged 65 years and older from four international cohorts were followed-up for mortality for an average of 10 years (8, 596 deaths). Data were harmonized across cohorts and mutually exclusive groups of disease combinations were created for cancer, myocardial infarction (MI), stroke, and diabetes at baseline. Cox proportional hazards models for all-cause mortality were used to estimate the age- and sex-adjusted hazard ratio and rate advancement period (RAP) (in years). Results: At baseline, 23.6% ( n = 5, 116) of participants reported having one condition and 4.2% ( n = 955) had two or more conditions. Data from all studies combined showed that the RAP increased with each additional condition. Diabetes advanced the rate of dying by the most years (5.26 years; 95% confidence interval [CI], 4.53–6.00), but the effect of any single condition was smaller than the effect of disease combinations. Some combinations had a significantly greater impact on the period by which the rate of death was advanced than others with the same number of conditions, for example, 10.9 years (95% CI, 9.4–12.6) for MI and diabetes versus 6.4 years (95% CI, 4.3–8.5) for cancer and diabetes. Conclusions: Combinations of cancer and cardiometabolic conditions accelerate mortality rates in older adults differently. Although most studies investigating mortality associated with multimorbidity used disease counts, these provide little guidance for managing complex patients as they age.